REVIEW OF ISLAMIC LAW ON THE PRACTICE OF RENTING A KOST ROOM IN CICALENGKA VILLAGE, BANDUNG DISTRICT - Rico Tira Andiansyah; Mulyana Mulus; Aulia Fadhil (STIESA Press, 2020)
Renting a place to stay in Rancaekek, Bandung Regency is a promising business field, and this business cannot be separated from any collaboration that will aim at the best agreement, where this collaboration is carried out between the tenants and the boarding house rental business owners. The composer chose the research location in Cicalengka Kelurahan, because in that area the majority of the population had a boarding house rental business, and the population had a boarding house rental business, and the area had a fairly high level of migrants. As for the main problem, how is the contract to implement the practice of renting is legal or not according to Islamic law, and has it reached an agreement on the fair price and the term of the lease determined by both? And what if there is a default in the implementation of this rental practice? To answer the question above the research method used is the type of field research, the nature of this study included in descriptive abalytic that is describing the practice of renting and clearly describing the problems contained in this study and assessing the research in a review of Islamic law. Data collection techniques with direct observation, interviews and supported by data taken from relevant data sources. The findings of this study indicate that the agreement that occurs between the tenant and the owner of the rented room is done verbally and in writing. This is done in accordance with Islamic law by meeting the pillars and conditions. For determining the price and rental period, it has been determined based on various facilities provided, such as physical and non-physical facilities. Where as the default contained in the practice of leasing is settled with a compensation agreed previously by both parties. To avoid violating the contents of the agreement, the terms or anything related to this agreement must be clearly written so that in the future it will not cause confusion and misunderstanding. And the government should also participate in regulating the practice of renting by making regulations or clarifying norms in the community, so that later in can create a safe and comfortable atmosphere in social life.